User Experience Evaluation On The McDonald's Application Using The User Experience Questionnaire Method: Evaluasi User Experience Pada Aplikasi Mcdonald’s Menggunakan Metode User Experience Questionnaire - Fadhilah Shabuhalaika Aliyya; Aries Dwi Indriyanti (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
In the rapidly evolving digital era, McDonald's launched a mobile app in 2019 as an effort to provide consumers with ease and convenience in accessing its fast food services. This app is designed to allow users to place orders, enjoy exclusive promotions, participate in loyalty programs, and obtain various other services more practically. However, the McDonald's app faces various technical issues that disrupt user convenience, such as transaction failures, login difficulties, and application instability, which impact the user experience and affect their satisfaction levels. This study involved 412 respondents who are active McDonald's app users. The evaluation results using the User Experience Questionnaire (UEQ) method showed that the McDonald's app obtained an average score that was categorized as "Bad" when compared to the UEQ benchmark. The dimensions of Efficiency (-0,989), Attractiveness (-0,879), and Dependability (0.178) indicated low user perceptions of the app's speed, visual appeal, and reliability in conducting transactions. Meanwhile, the Perspicuity dimension (0,054) is in the neutral category, and the Stimulation (0.837) and Novelty (0.601) dimensions are in the "Below Average" category. Based on these findings, several recommendations for improvement are proposed to improve the user experience of the McDonald's application, including: redesigning the application interface to be more attractive and aesthetic, simplifying the navigation flow to be more intuitive, optimizing system performance to increase processing speed, and increasing the reliability and stability of the application in transactions.